Rab11 is required for cell adhesion, maintenance of cell shape and actin-cytoskeleton organization during Drosophila wing development. - Bhuin, T.; Roy, J.K. (International Journal of Developmental Biology, 2011)
Intracellular protein trafficking is a key factor in maintaining epithelial cell adhesion and cell shape. Small monomeric Rab GTPases are key players involved in intracellular membrane transport. Rab11, a subfamily of the Ypt/Rab gene family of ubiquitously expressed GTPases, is associated with recycling endosomes, and acts as a master molecule in regulating vesicular trafficking. Wing epithelium of Drosophila has been chosen to address the involvement of Rab11 in trafficking of a cell adhesion molecule, the ?PS integrin. Here, we show that Rab11 immunocolocalizes with trans-Golgi network and it is enriched in the centrosomal/recycling endosomal area labeled by ?-Tubulin. Furthermore, Rab11 is required for transcytic and exocytic trafficking of ?PS integrin; alterations of Rab11 function by different genetic procedures in wings results in the formation of blisters. We show altered activity of Rab11 affects cell adhesion, cell shape and organization in the actin-cytoskeleton during wing morphogenesis. Finally, using a genetic approach, we demonstrate that Rab11 interacts with the ?PS integrin. Collectively, our data suggest that Rab11 regulates cell adhesion, maintenance of cell shape and actin-cytoskeleton organization during Drosophila wing development.